2012
DOI: 10.1021/ja3079972
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic and Photothermal Effects of Semiconducting and Metallic-Enriched Single-Walled Carbon Nanotubes

Abstract: Semiconducting and metallic single-walled carbon nanotubes (s-SWNTs and m-SWNTs) were enriched by agarose gel chromatography and their photothermal and photodynamic effects were compared in H(2)O. Under near-infrared laser irradiation, s-SWNTs generated reactive oxygen species (ROS) more than m-SWNTs, whereas m-SWNTs produced heat more efficiently than s-SWNTs. More importantly, cancer cell killing by PDE of s-SWNTs has been disclosed for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
138
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(139 citation statements)
references
References 38 publications
0
138
0
1
Order By: Relevance
“…It should be noted that the single-CNT method is not limited to the reversible activation of protein function. The reversible mode becomes irreversible simply by extensive heating at >40°C, which inactivates most proteins irreversibly through thermal denaturation, as demonstrated for ablating cancer cells (Kam et al 2005;Biris et al 2009;Murakami et al 2012). Inoue et al (2015) used a constant concentration of oxygen Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that the single-CNT method is not limited to the reversible activation of protein function. The reversible mode becomes irreversible simply by extensive heating at >40°C, which inactivates most proteins irreversibly through thermal denaturation, as demonstrated for ablating cancer cells (Kam et al 2005;Biris et al 2009;Murakami et al 2012). Inoue et al (2015) used a constant concentration of oxygen Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although a concrete mechanism of CNT toxicity is still open to discussion, the CNTinduced generation of reactive oxygen species (ROS) may be a key factor to induce DNA damage and protein modifications (Pacurari et al 2008;Liu et al 2011). CNT toxicity can be strongly enhanced by laser irradiation, which generates both heat and ROS to kill cancer cells (Kam et al 2005;Murakami et al 2012). In some biological applications, CNT toxicity can be minimized by reducing agglomerate CNT structures (Pauluhn 2010) and by processes that functionalize the CNT surface, such as the chemical formation of organometallic structures (Chen et al 1998;Cui et al 2004) or noncovalent coatings with phospholipid-polyethylene glycols or other amphiphilic surfactant molecules (Liu et al 2007).…”
Section: Cnt Toxicity In Biological Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…50 In the irradiation therapeutic window using laser parameters, as was applied during this study, the effect was mostly athermic with limited heat transfer (0.65°C).…”
mentioning
confidence: 90%
“…Another research group also analyzed the photodynamics of (6,5)-SWNTs suspended in H 2 O with another polymer, to determine the triplet state lifetime (30±10 µs) and the quantum yield of triplet formation (5±2%). 64) Our group has revealed that semiconducting SWNTs of high purity are able to generate 1 O 2 and O 2 · − in H 2 O containing 1 wt% sodium deoxycholate under NIR illumination at 808 nm 65) (Fig. 8).…”
Section: Optical Properties Of Swntsmentioning
confidence: 99%